Performance evaluation for JPEG compression on model-based source camera identification - Bo WANG; Jian-feng YIN; Ya-bin LI (网络与信息安全学报)
Focusing on JPEG images transferred by social platform and network media from actual forensic cases,quantities of simulation experiments were carried out to evaluate the performance of three typical methods of model-based source camera identification.The methods are based on the feature of interpolation coefficients of color filter array(CFA),local binary pattern(LBP),and image quality measurement(IQM)with high-order wavelet statis-tic features.The experiments demonstrate that the accuracy decreases rapidly with the compression quality of im-ages decreasing.As a result,methods of model-based source camera identification currently used are demanded bet-ter performance in practical scenes.